2015
DOI: 10.1097/bot.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Relationship Between the Spermatic Cord and the Pubic Tubercle

Abstract: The spermatic cord is located lateral and immediately adjacent to the pubic tubercle after it exits the inguinal canal and passes into the scrotum. As such, the spermatic cord seems to be at a significant risk of sustaining injury when pointed forceps are placed on the tubercles, as is often recommended during the repair of pubic diastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Our ndings showed that the exit point to symphysis pubis distance is smaller in male patients (16mm) than females (24.1mm), which is similar to what was previous reports [8, 10,11]. This nding makes pudendal nerve injury more likely in males than females since it exits 0.8 mm (range 0-2 mm) lateral to the pubic tubercle [14]. This is an important consideration to avoid potential sexual dysfunction in male patient.…”
Section: Discussionsupporting
confidence: 89%
“…Our ndings showed that the exit point to symphysis pubis distance is smaller in male patients (16mm) than females (24.1mm), which is similar to what was previous reports [8, 10,11]. This nding makes pudendal nerve injury more likely in males than females since it exits 0.8 mm (range 0-2 mm) lateral to the pubic tubercle [14]. This is an important consideration to avoid potential sexual dysfunction in male patient.…”
Section: Discussionsupporting
confidence: 89%
“…The distance between the cable and the obturator canal was 3.0–3.5 cm. Interference with the spermatic cord/round ligament or the femoral vessels should be considered 24 .
Figure 6 Anatomical landmarks.
…”
Section: Resultsmentioning
confidence: 99%
“…As previously described by Hadeed et al, some important anatomical structures must be considered 49 . In particular, the spermatic cord and ligamentum suspensorium penis in men and the round ligament, clitoral body, and clitoral glans in women must be spared to prevent dyspareunia, erectile dysfunction, or infertility [50][51][52][53] . During our dissection, we identified no conflict with the abovementioned structures.…”
Section: Discussionmentioning
confidence: 99%